Implementing HIV teams to improve HIV indicator condition-guided testing in general practitioner centers in the Netherlands - Jordans, Carlijn C. E.; Niemantsverdriet – Rokx, Lotte; Struik, Jan L.; van der Waal, Eva C.; van der Voorn, Paul V. J. M.; Bakker, Nienke; Verbon, Annelies; Bindels, Patrick J. E.; Rokx, Casper (BMC family practice, 2024)
Background HIV indicator condition-guided testing is recommended by guidelines to identify undiagnosed HIV infections. However, general practitioners (GPs) frequently see patients for indicator conditions without testing them for HIV. The aim of this study was to evaluate whether implementing HIV teams, using trained GP ambassadors, promoted local HIV indicator condition-guided testing practices in urban GP centers in the Netherlands. Methods We conducted a prospective implementation study between May 2021 and March 2023. Patients ≥ 18 years newly diagnosed with HIV indicator conditions in three GP centers were included. The intervention consisted of HIV expert led education for GPs with a stepwise implementation of point-of-care testing (phase 1), followed by adding peer-to-peer case feedback by trained GP ambassadors (phase 2). Questionnaires were used to assess the experiences and beliefs of HIV indicator condition-driven testing in patients and GPs. The primary outcome was the overall HIV testing rate in patients diagnosed with indicator conditions compared to pre-implementation. Secondary outcomes were HIV testing rate per phase and per indicator condition, HIV positivity rate, and patients’ and GPs’ experiences with this testing strategy. Results In 132,338 patient visits, 846 (0.6%, 95%CI 0.6–0.7%) HIV indicator conditions were diagnosed, including 485 sexually transmitted infections (57.3%). Overall, 215 (25.4%) indicator conditions were tested for HIV after the implementation of HIV teams. The testing rate was comparable between the two phases (25.2% versus 25.9%, p = 0.83). The testing rates pre- and post-implementation were comparable (21.3% versus 25.4%, p = 0.33). The most frequently tested HIV indicator conditions were unexplained weight loss ( n = 13, 41.9%), unexplained lymphadenopathy ( n = 8, 38.1%), and sexually transmitted infections ( n = 161, 33.2%). Three patients (1.4%, 95%CI 0.3–4.0%) tested positive for HIV. Test acceptance in patients was high as was the self-perceived knowledge of GPs on HIV indicator conditions. Conclusions Implementing HIV teams did not enhance HIV indicator condition-guided testing in urban GP centers from a low HIV prevalence setting. The high patients acceptance rate and self-perceived knowledge among GPs regarding HIV indicator conditions did not manifest in high HIV testing rates. Patients accepted testing, but a gap was found between the self-perceived knowledge of GPs regarding HIV indicator conditions and testing, and the actual HIV testing rate. Trial registration ClinicalTrials.gov NCT05225493 (registration date: 17-01-2022).